2022
DOI: 10.3390/molecules27206940
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Artocarpus lacucha Focusing on the Phytochemical Constituents and Pharmacological Properties of the Plant

Abstract: Studies have shown that approximately two-thirds of the plant species in the world have some medicinal value. Artocarpus lakoocha is a synonym for Artocarpus lacucha and is a plant that can be found in Indonesia. This medicinal plant has been used to treat many diseases. (1) Objective: This article discusses the scientific investigations carried out on A. lacucha, namely the plant’s chemical content, pharmacological activity, and active compounds. (2) Methods: The design of this study was based on an article t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In addition to its culinary uses, monkey jack has also been used in traditional medicine for various purposes, including the treatment of asthma, anemia, dermatitis, diabetes, and diarrhea (Jagtap and Bapat 2010). Previous studies have shown that A. lacucha contains high levels of flavonoids and phenolic compounds, particularly in the ethyl acetate and methanol extracts of the leaves and bark (Duangdee et al 2019, Songoen et al 2021, Sitorus et al 2022). The bark extract has also been found to contain a number of specific compounds, including afzelechin-3-O-RL rhamnopyranoside, amyrin acetate, dihydromorin, (–)-epiafzelechin, lupeol acetate, oxyresveratrol, and catechin (Saowakon et al 2009, Islam et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its culinary uses, monkey jack has also been used in traditional medicine for various purposes, including the treatment of asthma, anemia, dermatitis, diabetes, and diarrhea (Jagtap and Bapat 2010). Previous studies have shown that A. lacucha contains high levels of flavonoids and phenolic compounds, particularly in the ethyl acetate and methanol extracts of the leaves and bark (Duangdee et al 2019, Songoen et al 2021, Sitorus et al 2022). The bark extract has also been found to contain a number of specific compounds, including afzelechin-3-O-RL rhamnopyranoside, amyrin acetate, dihydromorin, (–)-epiafzelechin, lupeol acetate, oxyresveratrol, and catechin (Saowakon et al 2009, Islam et al 2019).…”
Section: Introductionmentioning
confidence: 99%